Pedagogical Insights into the Impact of Gadget Use on Social-Emotional Development in Early Childhood - Rohana; Reswita (International Journal of Pedagogy, 2025)
This study explores the impact of gadget use on the social-emotional development of early childhood, a crucial stage for developing emotional regulation, social interaction skills, and empathy. With rapid technological advancements and the increasing use of gadgets among children, concerns have emerged regarding their effects on children's social-emotional development. A descriptive qualitative approach was used in this study, utilizing observation, interviews, and documentation techniques to collect data from 3-6 years old children in several early childhood education institutions. The results show that excessive gadget use negatively affects social-emotional development, characterized by reduced social interaction skills, difficulty regulating emotions, and low empathy. Children who frequently engage with gadgets also tend to display withdrawn behaviors and high dependence on digital devices. These findings highlight the essential role of parents and educators in limiting gadget use and ensuring children experience adequate social interactions to foster healthy emotional development. The study underscores the need for balanced and supervised gadget use to ensure children receive a well-rounded learning experience that supports their social-emotional growth.